Acute graft-versus-host disease associated cerebellitis as the cause of pyrexia of unknown origin detected with 18F-FDG-PET/CT. (2021) - Jewell, Kerry E.; Kuzich, James A.; Lee, Sze Ting; Trethowan, Rebecca; Macdonell, Richard; Schwarer, Anthony P.
Highlights: Graft versus host disease of the central nervous system (CNS-GVHD) is a controversial entity, and its diagnosis is often hampered by the absence of a histological specimen. The structural and functional imaging characteristics of CNS-GVHD are poorly described. We present the first description of acute CNS-GVHD manifesting as cerebellitis, associated with marked cerebellar hypermetabolism on 18 F-fluorodeoxyglucose PET/CT (FDG-PET). FDG-PET may have a role in investigating pyrexia of unknown origin following allogeneic stem cell transplant.